Common cranes Grus grus and habitat management in holm oak dehesas of Spain - Aviles, J M (BIODIVERSITY AND CONSERVATION, 2004)
Changes in agricultural policies have favored tree clearing and removal of shrubs to favor intensive farming in the holm oak Quercus ilex dehesas of Iberia. The effect of these changes for bird species wintering in this agricultural landscape has been rarely analyzed. Here the effects are studied of farming changes in traditional holm oak dehesas on population size, social structure and time budget of common cranes Grus grus in eight traditional wintering sites in Spain. The role of acorn availability, the principal winter food of the species, in relation to management is also assessed. The number of cranes in each wintering area was not related to degree of agricultural intensification, nor to the availability of acorns. However, crane flock size decreased, and the relative occurrence of isolated family groups increased in less intensively transformed wintering areas characterized by the predominance of fallow lands. The age composition of crane flocks varied with acorn availability since more juveniles were reported in areas with relatively lower acorn availability. Time budget was also related to acorn availability, since cranes spent relatively more time preening in those wintering areas with higher availability of acorns. Globally evidence suggests the need to maintain the fallow land (posios) to sustain the wintering populations of cranes in Iberia, since this agro-grazing system maintains most of the juvenile cranes using the western migratory route.
Keywords: acorns; agricultural policies; holm oak dehesas

Common cranes Grus grus and habitat management in holm oak dehesas of Spain - Aviles, J. M. (BIODIVERSITY AND CONSERVATION, 2004)
Changes in agricultural policies have favored tree clearing and removal of shrubs to favor intensive farming in the holm oak Quercus ilex dehesas of Iberia. The effect of these changes for bird species wintering in this agricultural landscape has been rarely analyzed. Here the effects are studied of farming changes in traditional holm oak dehesas on population size, social structure and time budget of common cranes Grus grus in eight traditional wintering sites in Spain. The role of acorn availability, the principal winter food of the species, in relation to management is also assessed. The number of cranes in each wintering area was not related to degree of agricultural intensification, nor to the availability of acorns. However, crane flock size decreased, and the relative occurrence of isolated family groups increased in less intensively transformed wintering areas characterized by the predominance of fallow lands. The age composition of crane flocks varied with acorn availability since more juveniles were reported in areas with relatively lower acorn availability. Time budget was also related to acorn availability, since cranes spent relatively more time preening in those wintering areas with higher availability of acorns. Globally evidence suggests the need to maintain the fallow land (posios) to sustain the wintering populations of cranes in Iberia, since this agro-grazing system maintains most of the juvenile cranes using the western migratory route.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: KLUWER ACADEMIC PUBL
Keywords: acorns; agricultural policies; holm oak dehesas